Penentuan Nilai Faktor Mesin Pesawat Sinar-X Radiografi Digital Merek Shimadzu di RSUD Dr. Kanujoso Djatiwibowo Balikpapan - Mamba'ul Fitriyana; Suhadi Muliyono; Kadek Subagiada (Progressive Physics Journal, 2020)
The research on the determining machine factor (k) of Shimadzu digital radiograph X-ray machine have been done at the RSUD Dr. Kanujoso Djatiwibowo Balikpapan. Machine factor should be required in the calculation of radiation exposure which produced by the X-ray machine. Measurement data that have been used as independent variables were current-time, focus distance to the detector and tube voltage variations of 80 kV to 100 kV, while the dependent variable was the S value. Determination of the k value was conducted by weighted linear regression between V2 and using the results of research by Seibert and Morin (2011) for the condition of calibrated X-ray machine. Thus, the reseach has obtained the machine factor of the Shimadzu digital radiograph X-ray machine at the RSUD Dr. Kanujoso Djatiwibowo Balikpapan.